ENHANCING COMPETITIVENESS THROUGH CREATIVITY AND CULTURAL HERITAGE: A COMPARATIVE STUDY OF MICRO- AND SMALL-SCALE HANDICRAFT ENTERPRISES IN SOUTHEAST ASIA - Nurdiana Mulyatini; M. Mima Villanueva; Elin Herlina; M. Zaki Rahman; Risna Kartika (Multifinance, 2026)
Micro and small craft enterprises (MSEs) play a crucial role in promoting sustainable competitiveness in the Southeast Asia region. This study aims to explore how creativity and cultural heritage management contribute to the competitiveness of micro and small enterprises through a comparative analysis. Using a qualitative approach, field observations, interviews, and focus group discussions were conducted in Ciamis, Indonesia, and Negros Occidental, the Philippines. Thematic and comparative analyses were applied to identify creativity-based strategies, innovation practices, and institutional support. The findings show that Indonesian MSEs emphasize heritage-based collaboration and authenticity, while Filipino enterprises focus on design-led innovation and export- oriented storytelling. Both contexts face challenges in digital transformation and sustainability. This study proposes an integrative framework for enhancing creative competitiveness by combining cultural heritage, creativity management, and innovation ecosystems across Southeast Asia.